Perceived Difficulty with Physical Tasks, Lifestyle, and Physical Performance in Obese Children. (3rd July 2014) - Valerio, Giuliana; Gallarato, Valeria; D'Amico, Osvaldo; Sticco, Maura; Tortorelli, Paola; Zito, Eugenio; Nugnes, Rosa; Mozzillo, Enza; Franzese, Adriana
Abstract : We estimated perceived difficulty with physical tasks, lifestyle, and physical performance in 382 children and adolescents (163 obese, 54 overweight, and 165 normal-weight subjects) and the relationship between perceived physical difficulties and sports participation, sedentary behaviors, or physical performance. Perceived difficulty with physical tasks and lifestyle habits was assessed by interview using a structured questionnaire, while physical performance was assessed through the six-minute walking test (6MWT). Obese children had higher perceived difficulty with several activities of daily living, were less engaged in sports, and had lower physical performance than normal-weight or overweight children; on the contrary, they did not differ with regard to time spent in sedentary behaviors. Perceived difficulty in running and hopping negatively predicted sports participation (P < 0.05 and <0.01, resp.), while perceived difficulty in almost all physical activities negatively predicted the 6MWT, independently of BMI (P < 0.01 ). Our results indicate that perception of task's difficulty level may reflect an actual difficulty in obese children. These findings may have practical implications for approaching physical activity in obese children. Exploring both the perception of a task's difficulty level and physical performance may be useful to design exercise programs that allow safe and successful participation.